Exterior view of the Mukhamandapa of the Mahakal Temple - Temples of India Project Team (Jio Institute, 2024)
The mukhamandapa (front porch) of the Mahakal Temple features a kakshasana (seat backs) adorned with niches housing divine figures, including deities like Brahma and Kaumari. Interwoven among these divine figures are depictions of ascetics, musicians, and surasundaris (celestial damsels).